Report on mining development plan of Iscaycruz (Oyon) area - Japan International Cooperation Agency (1986)
Complying with the Peruvian Government request in 1985, preliminaly survey as well as the subject feasibility study, infrastructure to be related to develop the mine and economic intention for the district was conducted at the Iscaycruz district, which indicated high potentiality of occurrence of copper, lead and zinc deposits under the scheme of "Cooperative Mineral Exploration" since 1979. The survey was carried out by the feasibility study team which comprised with six specialists from Japan International Cooperation Agency (JICA) and Metal Mining Agency of Japan (MMAJ) as a special participant together with the five Peruvian counter partners of Instituto Geológico Minero y Metalúrgico (INGEMMET).